HIV self‐testing and repeat testing in pregnancy and postpartum in Northern Nigeria. Issue 1 (4th January 2022) - Iliyasu, Zubairu; Galadanci, Hadiza S.; Musa, Abubakar H.; Iliyasu, Bilkisu Z.; Nass, Nafisa S.; Garba, Rayyan M.; Jibo, Abubakar M.; Okekenwa, Sonia C.; Salihu, Hamisu M.; Aliyu, Muktar H.
Abstract: Objective: Incident HIV infections in pregnant and breastfeeding mothers pose significant challenges to prevention of mother‐to‐child HIV transmission efforts in sub‐Saharan Africa. We identified the predictors of willingness to self‐test for HIV when retesting in pregnancy and postpartum among antenatal clients in a tertiary hospital in Northern Nigeria. Methods: Structured and validated questionnaires were administered to a cross section of antenatal attendees ( n = 370) in March 2021. Willingness to self‐test and adjusted odds ratios of potential predictors were generated from logistic regression models. Results: Of the 317 respondents who agreed to repeat HIV test during pregnancy, 29.3% ( n = 93) were willing to self‐test. Similarly, of those ( n = 350) willing to retest after delivery, 27.4% ( n = 96) were willing to self‐test. Willingness to self‐test during pregnancy was higher among respondents who were multiparous (2–4 births) (adjusted odds ratio, aOR = 2.40, 95% confidence interval CI, 1.14–6.43), employed (aOR = 1.49, 95% CI, 1.13–4.53) and those with at least secondary education (aOR = 2.96, 95% CI, 1.43–11.47). In contrast, willingness to self‐test was lower among those who were unaware of the husband's HIV status (aOR = 0.05, 95% CI, 0.02–0.13). Willingness to self‐test after delivery was higher among respondents who were married (aOR = 15.41, 95% CI, 3.04–78.2), multiparous (aOR = 2.01, 95% CI, 1.27–5.63), employed (aOR = 1.59, 95% CI, 1.08–2.35) and had at least to secondary education (aOR = 6.12, 95% CI, 1.36–27.47). In contrast, willingness to self‐test postpartum was lower among those who booked late (≥29 weeks) (aOR = 0.11, 95% CI, 0.022–0.52), those who were unaware of the risk of HIV transmission during breastfeeding (aOR = 0.29, 95% CI, 0.12–0.68) and participants who were unaware of the husband's HIV status (aOR = 0.076, 95% CI, 0.03–0.19). Conclusion: Willingness to self‐test for HIV in pregnancy and postpartum was low in this population and was influenced by risk perception, socio‐demographic and obstetric attributes. Communication interventions and training of potential mentor mothers among early adopters could improve self‐testing in this group and similar settings.